From Community to Text and Back. On Semiotics and Ant as Text-Based Methods for Fleeting Objects of Study - Annalisa Pelizza (Tecnoscienza, 2011)
This article illustrates a case study where the adoption of epistemological assumptions and data analysis techniques borrowed from both semiotics and ANT have enabled the researcher to transcend the limits that characterise traditional studies on online communities underpinned by a “sociology of the social” approach. Today, the very concept of “online community” seems to be at stake, to the point that it is no longer clear whether there exist online ties that are specific enough to be called “communitarian”. In order to analyse such an opaque and unstable object of study, innovative methods specifically developed to study fuzzy objects have to be devised and some epistemological questions have to be addressed. Approaches like semiotics and ANT turn out to be useful exactly because they use texts as “handles” to grasp heterogeneous, transient, objects of study. This article discusses in details a “funnel-like” method of analysis in a research field that has too often forgone the critique of epistemological assumptions inherited from other disciplines.